Serving PE Teachers’ Views on the Interface of Primary and Secondary School PE in Hong Kong: 香港在職體育教師對中小學體育課程銜接的意見 - LI, Chung; CRUZ , Alberto; KAM, Kevin Wai Keung (Asian Journal of Physical Education & Recreation, 2012)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This study explored the views of 296 serving physical education (PE) teachers concerning the interface of secondary and primary school PE in Hong Kong. Attached to the interpretive research perspective, questionnaire and follow-up telephone interviews were adopted for soliciting their views on the importance, measures taken and suggestions for improvement. The findings indicated that over 91% of serving PE teachers acknowledged the importance of interface for facilitating pupils’ learning. Similar articulations with the functions and content of school PE that facilitated the interface were found. Although 21% of them claimed that they had taken some measures for enhancing curricular interface, most of them were not systematic and well-planned. Thus, most PE teachers looked forward to a standardized curriculum stipulated by the Education Bureau as to ensure the effectiveness of the interface. The study suggests reinforcing teachers’ awareness of the interface of PE; considering the inclusion of PE in the internal school assessment for the Secondary School Places Allocation System and strengthening the interface from system, school and classroom levels. Consequently, it would enhance the learning and teaching in physical education. 本文旨在探討296位在職體育教師對中小學體育課程銜接的意見。研究以詮釋理念為依據，透過問卷及跟進電話訪談以顯證他們對體育課程銜接的重要性、實施措施和改善建議的意見。結果顯示九成一在職體育教師認同銜接對促進學生學習的重要性，認定學校體育功能和所教授內容相近，有利相關課程的銜接。雖然有百分之二十一在職體育教師表示已推展一些課程銜接措施，但有關銜接措施未見系統及計劃推行。大多數體育教師期望教育局能訂定一系列標準課程以確保其成效。本研究建議提升體育教師對課程銜接的醒覺性，考慮將體育納入為小學升中呈分試科目之一，並從系統、學校及課室等層面上優化中小學體育課程的銜接，促進學與教。